Adolescent spirituality under digital distraction: how self control shapes the effect of fear of missing out and school climate - Dimas Ibrahim Salam; Akif Khilmiyah; Fitriah M.Suud (Lentera Negeri, 2026)
The rapid expansion of digital technology has increased adolescents’ vulnerability to Fear of Missing Out (FoMO), potentially affecting their spiritual development. This study examined the structural relationships among FoMO, school climate, self-control, and adolescent spirituality, with self-control as a moderating variable. A quantitative cross-sectional study was conducted with 100 junior high school students selected through purposive sampling. Data were collected using a 28-indicator questionnaire on a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The measurement and structural models demonstrated satisfactory validity, reliability, and model fit. School climate had the strongest direct effect on adolescent spirituality, followed by FoMO and self-control. Self-control significantly moderated the relationships between both FoMO and school climate with adolescent spirituality. Higher self-control reduced the adverse effects of FoMO and enhanced the positive influence of a supportive school environment. These findings indicate that adolescent spirituality is shaped by the interaction of environmental and psychological factors. The study contributes an integrated structural model and highlights the importance of strengthening positive school climates and self-control development in character and spiritual education programs.